Empirical essays on digital platforms - Lena Marie Abou El-Komboz (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2025)
Digital platforms alter almost every industry in the modern economy (De Reuver et al., 2018). For instance, in the media industry, there is an increasing shift from traditional media outlets such as newspapers and television to online newspapers, social media, or platforms such as Netflix or YouTube to watch content (Waldfogel, 2017; Wu and Zhu, 2022). In the software industry, more digital by its nature, it is nowadays the standard to use version control systems such as git, with code stored on online platforms. These platforms emerged and now dominate the supply of online media, for instance, software, music, news, and videos (Waldfogel, 2017; Wu and Zhu, 2022). Three of the top 10 of the global 2000 list by Forbes in 2023 are platform companies, namely Alphabet (Google), Microsoft, and Apple (Cusumano et al., 2019; Bonina et al., 2021; Forbes, 2023). These companies are at the global top concerning sales, profits, assets, and market value, and simultaneously shape our economies. Some firms have started as a digital firm, whereas others have moved their business model in the spirit of the digital transformation towards the online space (Nagle, 2022). For business models with high transaction costs, digital platforms are capable to lead to a reduction of its costs, whilst creating a more flexible and further reaching place for transactions than traditional offline platforms (Sutherland and Jarrahi, 2018).
Keywords: D62; D83; H40; J24; J30; L17; L84; L86; O18; O30; O33; O36; R32; 330; high-skilled labor; geography; innovation; peer effects; collaboration; software; knowledge work; digital platforms; signaling; job search; social interactions; social multiplier; open source; platform governance; partnership programs; content supply; ad-based business models; access restrictions